2007
DOI: 10.1063/1.2783479
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature gas sensing properties of SnO2/multiwall-carbon-nanotube composite nanofibers

Abstract: Pure SnO 2 and SnO 2 polycrystalline nanofibers doped with multiwall carbon nanotubes ͑MWCNTs͒ are synthesized by electrospinning followed by calcination in air at 500°C. The measurement results by sensors fabricated from these fiber mats at steady state show that the n-type SnO 2 /MWCNT nanofibers are able to detect carbon monoxide at 50 ppm at room temperature, while the pure SnO 2 nanofibers are insensitive up to 500 ppm. The MWCNT doped SnO 2 nanofibers have demonstrated their potentials for wearable room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 29 publications
(23 reference statements)
1
41
0
Order By: Relevance
“…[20] We observed an increase in the conductivity of the sensor with exposure to CO and H 2 . This result is qualitatively consistent with what has been observed by Zhao et al [24] and Yang et al, [23] both of whom have attributed such response to the conversion of p-type CNTs to n-type CNTs. The assumption is that there are reactions between CO and O 2 adsorbates that lead to the flow of electrons back into the SnO 2 -CNT hybrid nanostructures, which would shift the Fermi level of the CNT away from the valence band toward the conduction band and would increase the sensor conductivity (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…[20] We observed an increase in the conductivity of the sensor with exposure to CO and H 2 . This result is qualitatively consistent with what has been observed by Zhao et al [24] and Yang et al, [23] both of whom have attributed such response to the conversion of p-type CNTs to n-type CNTs. The assumption is that there are reactions between CO and O 2 adsorbates that lead to the flow of electrons back into the SnO 2 -CNT hybrid nanostructures, which would shift the Fermi level of the CNT away from the valence band toward the conduction band and would increase the sensor conductivity (Fig.…”
supporting
confidence: 92%
“…[19] CNT surface functionalization, for example with Pd nanoparticles, [18] Pt nanoparticles, [20] or single-stranded DNA, [21] has been exploited to extend the spectrum of gases that CNT-based sensors can detect; however, these sensing materials are expensive and the type of gases that can be detected is still limited due to the selective catalytic activity of the surface functionalization. CNTs coated with a continuous SnO 2 film have been reported to sense NO 2 or CO, [22][23][24][25] but the fully encapsulated CNT cannot directly participate in the gas sensing, and thus, the sensitivity of the sensor is not maximized.…”
mentioning
confidence: 99%
“…In this regard, the fabrication of 215 nm diameter, succinic acidtreated chitosan/PAA composite fibrous membranes led to an 8-fold increase in sensitivity compared with thin film sensors, reaching a detection threshold as low as 50 ppm. 98 The high potential of electrospun fibers was also demonstrated by Yang et al, 99 who compared SnO 2 nanofibers with multiwalled carbon nanotube-doped SnO 2 fibers for detection of carbon monoxide. Where the pure SnO 2 fibers could not lead to any clear detection of carbon monoxide levels below 500 ppm, the inclusion of the carbon nanotubes boosted the sensitivity to below 50 ppm at room temperature, highlighting the importance of dopants for high sensitivity.…”
Section: Protein-responsive Electrospun Fibersmentioning
confidence: 88%
“…Next to proteins, even living cells such as bacteria and mammalian cells were safely encapsulated within electrospun fibers. Liu et al 126 reported on the fabrication of polyethylene oxide 99 -polypropylene oxide 67 -polyethylene oxide 99 triblock polymer fibers by electrospinning and the encapsulation of microbes from three industrially relevant genera (Fig. 15).…”
mentioning
confidence: 99%
“…Till now CNTs were embedded in numerous polymeric fibres [15] such as PS [16], PVA [17] and only in few types of ceramic nanofibres as SnO 2 [18], TiO 2 [19] and Al 2 O 3 [20]. The prepared nanofibrous composites are expected to exhibit an improved microwave absorption due to the better match between the dielectric loss and magnetic loss, which originates from the combination of paramagnetic CNTs and ferrimagnetic CoFe 2 O 4 , as suggested by Che et al in [3] in relation to CNTs/CoFe 2 O 4 particles nanocomposites obtained via CVD.…”
Section: Introductionmentioning
confidence: 99%